2018
DOI: 10.1002/chem.201802632
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Oxide Materials for Oxygen Evolution Catalysis via Single‐Source Precursor Chemistry

Abstract: The utilization of metal alkoxides as single-source precursors for (mixed-)oxide materials offers remarkable benefits, such as the possibility to precisely control the metal ratio in the resulting material, highly homogeneous distribution of the elements in the film, and the low temperatures required for film processing. Herein we report on the isolation and characterization of the bimetallic Co-Mo alkoxide [Co Mo O (OCH ) (dmf) ] (Co Mo ; dmf=N,N-dimethylformamide), which was prepared by the anion metathesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…3d transition metals and related materials have been intensively investigated as efficient electrocatalysts because of abundant resources and particular electronic configuration. [8][9][10][11][12][13][14][15][16][17] Among these promising catalysts, earthabundant Cu and Co based materials are highly desired for oxygen evolution reaction (OER). [18][19][20] For example, Kuznetsov et al and Tong et al fabricated bimetallic CoÀ Mo alkoxides and oxygen-deficient Co 3 O 4 quantum dots as efficient electrocatalysts to enhance the oxygen evolution electrolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3d transition metals and related materials have been intensively investigated as efficient electrocatalysts because of abundant resources and particular electronic configuration. [8][9][10][11][12][13][14][15][16][17] Among these promising catalysts, earthabundant Cu and Co based materials are highly desired for oxygen evolution reaction (OER). [18][19][20] For example, Kuznetsov et al and Tong et al fabricated bimetallic CoÀ Mo alkoxides and oxygen-deficient Co 3 O 4 quantum dots as efficient electrocatalysts to enhance the oxygen evolution electrolysis.…”
mentioning
confidence: 99%
“…[18][19][20] For example, Kuznetsov et al and Tong et al fabricated bimetallic CoÀ Mo alkoxides and oxygen-deficient Co 3 O 4 quantum dots as efficient electrocatalysts to enhance the oxygen evolution electrolysis. [13,14] Cao et al reported on the investigation of CuÀ Ni sulfide nanowires for improving water oxidation efficiency. [21] Chen et al investigated CuÀ Co(OH) 2 nanosheets having superior electrocatalytic activity with an OER overpotential of 300 mV at 10 mA cm À 2 .…”
mentioning
confidence: 99%
“…The drop‐casted precursor decomposed at an applied positive potential where Mo was completely lost from the films giving rise to high surface area films identified as cobalt oxo‐hydroxide. [ 93 ] Spiccia and his group received similar results for their electrodeposited [Ni(en) 3 ]Cl 2 (en = 1,2‐diaminoethane) precursor to form a NiO x ‐en film from a 0.10 m borate buffer (NaBi) solution (pH = 9.2). The NiO x ‐en films were more homogenous and had a higher electroactive surface area than films prepared from a simple Ni nitrate precursor, leading to more robust films with higher catalytic activity underlining the importance of the choice of molecular precursors.…”
Section: Ssp‐derived Electrocatalysts Toward Oer Her and Owsmentioning
confidence: 85%
“…Recently, 3d transition metal and their compounds are intensively investigated as efficient electrocatalysts due to their rich source and special d electronic configuration. 46,54,55,60,61,64,[157][158][159] Among all these promising catalysts, earth-abundant Cu and Co based materials are highly desired for OER. For example, Kuznetsov et al and Tong et al fabricated bimetallic Co-Mo alkoxide and oxygen-deficient Co3O4 quantum dots as efficient electrocatalysts to enhance the oxygen evolution electrolysis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kuznetsov et al and Tong et al fabricated bimetallic Co-Mo alkoxide and oxygen-deficient Co3O4 quantum dots as efficient electrocatalysts to enhance the oxygen evolution electrolysis, respectively. 54,55 Cao et al reported the investigation of Cu-Ni sulfide nanowires for improving the water oxidation efficiency. 56 Chen et al fabricated Cu-Co(OH)2 nanosheets having superior electrocatalytic activity with an OER overpotantial of 300 mV at 10 mA cm -2 .…”
Section: Introductionmentioning
confidence: 99%